Sorghum Carotenoid Variation - Bach, Tory; Bashir, Elfaddil; Cruet-Burgos, Clara; Rhodes, Davina (My University, 2019)
Purpose The purpose of this research is to understand the heritability and genetic controls of sorghum grain carotenoids in order to develop a biofortification plan. Hypothesis and Predictions • Hypothesis 1: Carotenoids in a genetically diverse sorghum association panel grown in a temperate humid environment are highly heritable. o Prediction 1: There will be a significant correlation in carotenoid content between sorghum grown in 2015 and 2016 measured by high-performance liquid chromatography (HPLC). o Prediction 2: Genome-wide association studies (GWAS) will identify some of the same quantitative trait loci (QTL) in each year, in particular zeaxanthin epoxidase (ZEP).
Keywords: USDA NIFA 2019-67032-29071